Hydrophobically associating polyacrylamide derivatives with double bond for enhanced solution properties. Issue 11 (15th September 2016) - Wu, Gang; Jiang, Xiaohui; Yu, Liangmin; Yan, Xuefeng
Abstract : A hydrophobically associating polyacrylamide with double bond P (AM‐MAA‐AMPS‐HDDE‐SA) (PAMAHS) has been synthesized by micellar copolymerization technique in mixed solvents (anhydrous ethanol and distilled water (1:10 by volume)) and characterized. The morphology and microstructure of PAMAHS copolymer observations show the formation of multilayer network‐like stacked structure, and the dissolution property and temperature resistance of the copolymer measurements show that PAMAHS has a good solubility and exhibits unique solution behavior. Due to the hydrophobic associations, the solution viscosity increases sharply when the polymer concentration exceeds a certain value. AFM confirms the existence of the polymer network structure in aqueous solution, and the enhancement of thermal stability of polymer is affirmed through TGA. Compared with the unmodified P (AM‐MAA‐AMPS‐SA) (PAMAS) copolymer, PAMAHS incorporation of capsaicin‐like monomer with biological activity is endowed with excellent antibacterial performance against Escherichia coli and Staphylococcus aureus . POLYM. ENG. SCI., 56:1203–1212, 2016. © 2016 Society of Plastics Engineers